PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV.B SDN 169 PEKANBARU - Putra, Oktomi Harjasa Putra Harjasa; Alpusari, Mahmud Alpusari; Kurniaman, Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated by the low result graders learn science IV.B SDN 169 Pekanbaru with an average of 63.88, with a minimum completeness criteria (KKM) IPA is 75. The number of students in grade IV.B are as many as 40 people, which reached KKM only 16 students with classical completeness 40%. This research is a classroom action research (PTK) which aims to improve the learning process in the classroom. Formulation of the problem: Does the application of inquiry learning model can improve learning outcomes IV.B grade science students SDN 169 Pekanbaru. The research was conducted on April 15 until May 18, 2015 with 2 cycles. Subjects were IV.B grade students of SDN 169 Pekanbaru numbering as many as 40 students were used as the data source. The data collection instruments are sikripsi teacher and student activity sheets as well as learning about the test results. Based on the implementation of the research with the implementation of inquiry learning model result teacher activity. The activities of teachers in the learning process in the first cycle the first meeting was 62.50%, at the second meeting of teacher activity was 66.66% and the third meeting rose as much as 12.51 becomes 75.00%. In the second cycle of increased activity of more teachers in the first cycle, the first meeting of the second cycle of teacher activity was 83.33% and in the second meeting of the second cycle increased to 87.50%. Results of the data analysis of student activity at the first meeting of the first cycle was 58.33%, the second meeting increased to 62.50%, and the third peretemuan increased to 75.00%. In the second cycle the first meeting of student activity is 87.50% and the second meeting of the second cycle increased to 91.66%. This thesis presents the results obtained from the value of learning daily tests before the procedure with an average 63.88, after rising action on the first cycle to 71.25 and increased by 11.54%, on the second cycle into 80.38 increased by 25.83%. Based on the results of the research with the implementation of inquiry learning model can improve learning outcomes IV.B grade science students SDN Pekanbaru. Key Words : Guided Inquiry Learning Model , Study Results IPA.